2022
DOI: 10.51458/bstd.2022.22
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antioxidant Capacities with the Phenolic and Flavonoid Contents of Royal Jelly Mixtures

Abstract: Royal jelly, which is used in functional foods due to its antioxidant capacity, has started to be widely used. In this study, the antioxidant capacities and phenolic contents of royal jelly mixtures were determined. Total phenolic substance contents (TPC) of royal jelly mixtures were specified using the Folin-Ciocalteu procedure, total flavonoid substance contents (TFC) by aluminium chloride colourimetric method, phenolic compound contents with LC-MS/MS and antioxidant activity with 2,2-diphenyl-1- picrylhydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Moreover, the author noted that the chemical composition was characterised by the predominance of chrysin (246.5-5501.1 µg/L) and caffeic acid phenethyl ester (165.1-2431.6 µg/L), while ferulic acid epicatechin, even detected in moderate concentrations, was not the main compound. However, similar to our study, quercetin was detected in low concentrations [68]. These differences regarding the chemical composition of royal jelly are easy to understand when samples from different regions of the world are characterised.…”
Section: Individual Polyphenols Content Detected By Lc-mssupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, the author noted that the chemical composition was characterised by the predominance of chrysin (246.5-5501.1 µg/L) and caffeic acid phenethyl ester (165.1-2431.6 µg/L), while ferulic acid epicatechin, even detected in moderate concentrations, was not the main compound. However, similar to our study, quercetin was detected in low concentrations [68]. These differences regarding the chemical composition of royal jelly are easy to understand when samples from different regions of the world are characterised.…”
Section: Individual Polyphenols Content Detected By Lc-mssupporting
confidence: 87%
“…The chemical variations from one sample to another were not noticeable. In contrast, Altun et al (2022) showed significant variations in the chemical composition of commercial royal jelly mixtures. Moreover, the author noted that the chemical composition was characterised by the predominance of chrysin (246.5-5501.1 µg/L) and caffeic acid phenethyl ester (165.1-2431.6 µg/L), while ferulic acid epicatechin, even detected in moderate concentrations, was not the main compound.…”
Section: Individual Polyphenols Content Detected By Lc-msmentioning
confidence: 82%